2022
DOI: 10.3390/ijerph191710787
|View full text |Cite
|
Sign up to set email alerts
|

Care Needs and Symptoms Burden of Breast Cancer Patients in Jordan: A Cross-Sectional Study

Abstract: Breast cancer is the most common malignancy in Jordan. Rigorous needs assessment for breast cancer patients can prioritize both cancer care and palliative care to propose the appropriate services effectively. We conducted a cross-sectional study of breast cancer patients in a cancer center in Jordan. We assessed symptom burden, comorbidities, and performance using the Edmonton Symptom Assessment System (ESAS), the Charlson Comorbidity Index (CCI), and the Australia-modified Karnofsky performance scale (AKPS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Cancer survivors and their family caregivers have specific needs and expectations regarding healthcare professionals' support. Although several studies explored the cancer survivors' needs and expectations (Berger et al, 2020;Kim et al, 2020;Johnston et al, 2021;Shamieh et al, 2022), the family caregivers' perspective is poorly understood. A previous study has identified that patients with advanced cancer and their family caregivers have unmet care needs regarding information, including illness, treatment, and care-related information (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer survivors and their family caregivers have specific needs and expectations regarding healthcare professionals' support. Although several studies explored the cancer survivors' needs and expectations (Berger et al, 2020;Kim et al, 2020;Johnston et al, 2021;Shamieh et al, 2022), the family caregivers' perspective is poorly understood. A previous study has identified that patients with advanced cancer and their family caregivers have unmet care needs regarding information, including illness, treatment, and care-related information (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with breast cancer may face significant impaired function and overall symptom burden especially in advanced stages. 20 …”
Section: Introductionmentioning
confidence: 99%
“… 31 , 32 The early integration is crucial, especially in countries with limited resources, like ours, and should be linked to local clinical practice guidelines (CPG) and process and outcome key performance indicators (KPI). 20 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations